Occupational Health and Safety Management System in Wastewater Treatment Plant Workers’ - Andi Nurwana; Andi Jamaluddin (International Journal of Economics, Business and Innovation Research, 2023)
Based on its type, this research is explanatory research which aims to analyze occupational health and safety and its impact on the occupational health and safety management system (OHSMS). There are 103 workers’ used as samples. The partial least squares (PLS-SEM) analysis with SmartPLS 3.0 software can be informs that occupational health can be improve OHSMS, because workers feel their health is guaranteed by the health insurance provided by the company. Respondents' assessment of indicators of equipment condition is seen as meeting the standard and can be used in work with the support of the senses possessed by workers, besides that the staying power shown by workers is in the high category so that it supports the implementation of work. The better the implementation of work safety at the site, the better the implementation of OHSMS. The management of Losari Wastewater Treatment Plant (WWTP) is fully committed to the protection of assets and work environment and workers. Protection for workers is intended so that workers carry out their duties safely. The work equipment used in work is in good condition, so as to guarantee security and safety at work so as not to cause work accidents and work productivity is maintained.